Media Interaktif Penyuluhan HIV/AIDS Berbasis Android: Android-Based Interactive Media for HIV/AIDS Education - Eka Pratiwi, Anggy; Sellyana, Ari; Suhaidi, Mustazihim (Sekolah Tinggi Teknologi Dumai, 2025)
Technological advances have developed very rapidly and quickly, one of which is the health sector. Developments in the health sector are not only regarding increasingly developed medical equipment, but also media outreach which functions to increase knowledge to the public that health is very important, for example HIV/AIDS. Based on data from the Dumai City Health Service, HIV/AIDS cases in Dumai City are quite high, where the number of HIV in Dumai City in 2023 will reach 551 cases and AIDS will reach 324 cases. This increase in cases is due to a lack of public awareness of the dangers of HIV. /AIDS, especially among high school/vocational school students in the city of Dumai. Students must understand the importance of reproductive health and avoid casual sex to prevent HIV transmission and risky sexual behavior. Researchers used the Multimedia Development Life Cycle (MDLC) method in conducting research with stages such as Concept, Material Collection, Creation, Testing, Distribution. This interactive research media is made in the form of an animated video. The results of the questionnaire questions showed that of the 20 respondents each was given 10 questions. The index value obtained from the calculation was 88.1% of the total 100%, so it can be concluded that the respondents